Chlorophyta de la Costa Pacífica de Costa Rica - Fernández, Cindy (2008)
Chlorophyta of the Pacific coast of Costa Rica. Recent collections at the Pacific coast of Costa Rica have increased the number of reported marine green algae. In this paper we present an updated list of the marine green algae of this coast, which is based on reports from literature, collection of the National Herbaria of Costa Rica and recent field sampling. Ecological and environmental aspects of the different species are also included. A total of 38 species of chlorophytes, distributed in 16 genera, 12 families y six orders were documented, including five new records to the marine flora of Costa Rica: Codium isabelae, Codium picturatum, Codium sp., Caulerpa serrulata, and Parvocaulis parvula. Different ecological and distribution characteristics of these species were compared and analyzed among the North Pacific upwelling area and the South Pacific high rate sedimentation site. Rev. Biol. Trop. 56 (Suppl. 4): 149-162. Epub 2009 June 30.